2013
DOI: 10.1186/1758-5996-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eight weeks of resistance training on the risk factors of metabolic syndrome in overweight /obese women - “A Pilot Study”

Abstract: BackgroundThe purpose of the present study was to examine the effects of eight weeks of resistance training (RT) on anthropometric, cardiovascular and biochemical risk factors of metabolic syndrome (MetS), and neuromuscular variables on overweight/obese women.MethodsFourteen middle-aged (33.9 ± 8.6 years) overweight/obese women (body mass index - BMI 29.6 ± 4.1 kg/m2) underwent 24 sessions (3 times/week) of a whole body RT program with 3 sets of 8–12 repetitions maximum (RM). The following variables were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
2
26
0
1
Order By: Relevance
“…The interval between exercise series, cited in 11 studies, ranged from 30 seconds to 3 minutes, with no predominance of a specific interval (Table 2). Only two articles cited the speed of execution (2"X2") 11,18 (a result not shown in the table). In the specific case of TRT, the BMI values showed significant reductions in 2 articles 10,27 , while in 7 other articles 11,13,14,16,17,25,35 they were unchanged.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The interval between exercise series, cited in 11 studies, ranged from 30 seconds to 3 minutes, with no predominance of a specific interval (Table 2). Only two articles cited the speed of execution (2"X2") 11,18 (a result not shown in the table). In the specific case of TRT, the BMI values showed significant reductions in 2 articles 10,27 , while in 7 other articles 11,13,14,16,17,25,35 they were unchanged.…”
Section: Resultsmentioning
confidence: 98%
“…In 2 studies 26,37 the BMI values tended to be reduced, although with no indication of statistical significance. In 5 articles 12,18,19,28,29 the BMI values increased, although not significantly (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have shown that declines in BMI can be found following resistance training, results were equivocal showing increases and no change in this variable [29,30]. These divergent results are not difficult to explain since, as Prentice and Jabb [31] have stated, BMI is merely a surrogate measure of body composition and an ineffectual measure of body fat in individuals who have increased muscle mass due to training.…”
Section: Discussionmentioning
confidence: 72%
“…Resistance trainings are recommended as effective tools in the prevention and treatment of metabolic diseases (30). This is based on evidence suggesting that resistance trainings improve muscle mass and increases GLUT-4, protein kinase B and glycogen synthase (31).…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al (2016) observed a significant improvements for glucose of older women after 8 weeks resistance training in both traditional and pyramidal systems (19) Ribeiro et al (2015) found that the glucose had a significant improvement after 8 weeks resistance training in older women with differing levels of resistance training experience (novice and advanced) (20). In a pilot research, Tibana et al (2011) found that plasma glucose, triglyceride and HDL-c levels in obese/overweight women were not significantly changed after 8 weeks (24 sessions, 3 sessions per week) (each exercise 3 rounds and each round 8-12 iterations) (30). However, after 7 weeks of high-intensityresistance-focused training, Russell et al (2014) reported that the fasting glucose levels were reduced in people with a family history of diabetes and the matched control group (32).…”
Section: Discussionmentioning
confidence: 99%